Effects of Low-Dose and Long-Term Treatment with Erythromycin on Interleukin-17 and Interleukin-23 in Peripheral Blood and Induced Sputum in Patients with Stable Chronic Obstructive Pulmonary Disease. (3rd April 2016) - Tan, Caimei; Huang, Huijuan; Zhang, Jianquan; He, Zhiyi; Zhong, Xiaoning; Bai, Jing
Abstract : Objective. To study the effects of low-dose and long-term treatment with erythromycin on IL-17 and IL-23, in peripheral blood and induced sputum, in patients with stable chronic obstructive pulmonary disease (COPD). Methods . Patients were randomly divided into placebo-treated group, group A (12 months of additive treatment with erythromycin, N = 18 ), and group B (6 months of additive treatment with erythromycin followed by 6 months of follow-up, N = 18 ). Inflammatory cells in induced sputum, pulmonary function, and the 6-minute walk distance (6MWD) were analyzed. Concentrations of IL-17 and IL-23 in peripheral blood and sputum were measured using enzyme-linked immunosorbent assays. Results . After treatment, sputum and peripheral blood concentrations of IL-17 and IL-23 significantly decreased in groups A and B compared with placebo-treated group. There were no significant differences after erythromycin withdrawal at months 9 and 12 in group B compared with placebo-treated group. An increase in 6MWD was observed after treatment. Conclusions . Erythromycin was beneficial and reduced airway inflammation in COPD patients. Underlying mechanisms may involve inhibition of IL-17 and IL-23 mediated airway inflammation. COPD patients treated with erythromycin for 6 months experienced improved exercise capacity. Finally, treatment for 12 months may be more effective than treatment for 6 months.